2020
DOI: 10.1002/tsm2.194
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity during pregnancy is associated with a lower number of perineal tears

Abstract: Complex processes such as pregnancy and childbirth can be decisive for the health and well-being of both the mother and newborn, both during the process and in their life thereafter. 1,2 During 9 months, almost the entire body of a pregnant woman must change to create an environment adequate for fetal growth and development. It cannot be guaranteed that these changes will occur successfully because there are many alterations and pathologies related to the nature of pregnancy that can develop. Accordingly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This makes sense because surgical incisions may be performed to limit the most serious injuries as has been previously evidenced in the scientific literature [36]. Specific exercise and maintenance of adequate levels of physical activity throughout pregnancy may perhaps protect the perineal area [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes sense because surgical incisions may be performed to limit the most serious injuries as has been previously evidenced in the scientific literature [36]. Specific exercise and maintenance of adequate levels of physical activity throughout pregnancy may perhaps protect the perineal area [3].…”
Section: Discussionmentioning
confidence: 99%
“…International rates of 85% have been reported for perineal injuries [2], produced either spontaneously, such as tears, or deliberately because of an episiotomy. Recently, the frequency of the appearance of these lesions have been high in Spain, with a prevalence of 59% for tears [3] and between 19% and 50% for episiotomies [4]. The basic function of the episiotomy is to prevent perineal tears due to the tension caused by the mechanisms of labor, especially in primiparous pregnant individuals with instrumental delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such benefits include improved cardiovascular fitness, maintaining body mass, and maternal psychosocial well-being, [1][2][3][4] as well as a decreased risk of preeclampsia, gestational hypertension, and gestational diabetes. 5 Exercise engagement during pregnancy has also been associated with fewer newborn complications, 5 a reduced risk of cesarean delivery, instrumental delivery, and perineal tears, 5,6 as well as increased pelvic floor muscle strength, 7 which has been linked with decreased urinary incontinence. 8 Exercise in the postpartum period appears to reduce a woman's recovery time 9,10 and increases the likelihood of active offspring, setting up long-term positive health behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, pregnant women were advised against physical exercise since it was believed to be harmful to their health and may result in miscarriage, low birth weight, or early delivery. However, recent research has found that regular physical activity during pregnancy has several benefits for both the mother and the fetus [7][8][9][10]. Many recommendations encourage frequent, moderateintensity exercise as an integral part of maternal preventive care [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%